Preparation method of two-dimensional ion pair membrane and its application
By introducing polycarboxylic acid and polypyridine molecules to form ion pairs on the graphene oxide film, the problem of easy swelling in water and poor interception of monovalent ions is solved, and high salt retention rate and high water are achieved A two-dimensional ion pair film with flux is suitable for use in the desalting process.
Patent Information
- Application Number
- CN202211253640.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-10-13
AI Technical Summary
The existing graphene oxide films are prone to swelling in water, which are difficult to apply in actual desalination process, and have poor interception effect on monovalent ions and AB type ions, low water flux, and poor controllability of the film making process.
By adding vinyl-containing acid and amine monomers to the graphene oxide nanosheet dispersion, a radical polymerization reaction is carried out to form P1@GO and P2@GO nanosheet dispersions, which are deposited on a porous substrate in combination with nanosheet assembly technology. On the membrane, a two-dimensional ion pair film was prepared, and ion pairs were formed using polycarboxylic acid and polypyridine molecules to stabilize the layer spacing and improve hydrophilicity.
It significantly improves the salt retention rate and water flux, especially has a high retention effect on AB and A2B ions. The water flux reaches 28.2kg·m-2·h-1 at 60°C, and the membrane-forming process is controllable. Strong, suitable for mass production.
Smart Images

Figure CN115608175B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of membrane separation, and in particular to a preparation method of a two-dimensional ion pair membrane and application thereof. Background technology:
[0002] In recent years, due to the rapid development of the global economy, human demand for water resources has increased. However, frequent droughts and water pollution have exacerbated the global shortage of fresh water resources. Seawater accounts for about 97% of the world's water and is abundant in resources. Therefore, seawater desalination technology can effectively solve the problem of fresh water shortage and is expected to provide more fresh water for humans. At present, seawater desalination technology mainly includes distillation, freezing and membrane separation technology. Among them, membrane separation technology has attracted widespread attention due to its simple operation, low energy consumption and environmental friendliness, and is expected to replace traditional separation technology.
[0003] The core of membrane separation technology is the selection of membrane materials. Two-dimensional graphene oxide (GO) has regular interlayer channels and contains rich oxygen-containing functional groups such as hydroxyl, carboxyl and epoxy groups, which provide reaction sites for various modifications of graphene oxide. Through further modification, researchers can easily regulate the microstructure and chemical properties of graphene oxide membranes, so it has received widespread attention. However, due to the presence of these oxygen-containing functional groups, graphene oxide membranes are very easy to swell in water. As introduced in the literature (ACS Nano, 2017, 11 (6): 6440-6450), the interlayer spacing of graphene oxide membranes is only about 0.8nm in the dry state, while it will increase to 1.35nm in the wet state, and can even reach 6 to 7nm. Therefore, graphene oxide separation membranes are difficult to be applied in actual desalination processes.
[0004] Nature Communications (2019, 10(1): 1-8) improves the desalination capacity of graphene oxide membranes by regulating the surface charge of the membrane. By coating a layer of positively or negatively charged polymer on the surface of the graphene oxide membrane, the retention of AB2 (such as MgCl2) or A2B (such as Na2SO4) type ions is improved.
[0005] Journal of the American Chemical Society (2021, 143(13): 5080-5090) uses plasma technology to treat graphene oxide membranes to obtain graphene oxide membranes functionalized with nitrogen-rich functional groups. Compared with the original graphene oxide membrane, the functionalized graphene oxide membrane has significantly improved selectivity for monovalent / multivalent cations. However, these two strategies do not have a good retention effect on monovalent ions and AB (such as NaCl, etc.) type ions.
[0006] Patent CN112957929A discloses a preparation method and application of a modified graphene oxide membrane based on anion and cation regulation. The method sequentially immerses the graphene oxide membrane in anion / cation solutions for modification to obtain a modified graphene oxide membrane. Although the modification method can inhibit the swelling of the graphene oxide membrane, the water flux of the modified graphene oxide membrane is low during the pervaporation desalination process, which is only 6.24 kg·m at 70°C. -2 ·h -1 ; Moreover, the film-making process has poor controllability, which is not conducive to mass production. Summary of the invention:
[0007] In view of the deficiencies of the prior art, the present invention provides a method for preparing a two-dimensional ion pair membrane, aiming to obtain a two-dimensional ion pair membrane with higher salt rejection rate and water flux.
[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0009] One of the purposes of the present invention is to provide a method for preparing a two-dimensional ion pair membrane, comprising: adding a vinyl acid monomer to a graphene oxide nanosheet dispersion, and carrying out a free radical polymerization reaction under the initiation of an initiator to obtain a P1@GO nanosheet dispersion; adding a vinyl amine monomer to the graphene oxide nanosheet dispersion, and carrying out a free radical polymerization reaction under the initiation of an initiator to obtain a P2@GO nanosheet dispersion; and then mixing the P1@GO nanosheet dispersion and the P2@GO nanosheet dispersion in proportion and depositing the mixed mixture on a porous substrate membrane by a nanosheet assembly technique to obtain a two-dimensional ion pair membrane.
[0010] Preferably, the porous substrate membrane is selected from one of porous films such as nylon membrane, polyethersulfone membrane, polyvinylidene fluoride membrane, polycarbonate membrane, anodized aluminum membrane, polyacrylonitrile membrane, etc., and the pore size of the porous substrate membrane is 50-450nm.
[0011] Preferably, the vinyl-containing acid monomer is a vinyl-containing carboxylic acid or sulfonic acid monomer.
[0012] More preferably, the vinyl-containing acid monomer is acrylic acid (AA), p-styrenesulfonic acid (SS), propylenesulfonic acid (PSA) or 4-vinylbenzoic acid (4VBA), but is not limited thereto.
[0013] Preferably, the vinyl-containing amine monomer is a vinyl-containing pyridine or tertiary amine monomer.
[0014] More preferably, the vinyl-containing amine monomer is 4-vinylpyridine (4VP), dimethylallylamine (DMAA) or 4-dimethylaminostyrene (4DAS), but is not limited thereto.
[0015] The graphene oxide nanosheet dispersion is prepared by ultrasonically dispersing graphene oxide powder in deionized water or an organic solvent.
[0016] Preferably, the concentration of the graphene oxide nanosheet dispersion is 0.05-1 mg·mL -1 .
[0017] Preferably, the temperature of the ultrasound is 20-50°C and the time is 0.5-3h.
[0018] Preferably, the organic solvent is one of N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide, but is not limited thereto.
[0019] Preferably, the mass ratio of the graphene oxide nanosheets to the vinyl-containing acid monomer is 1:(1-200), and the mass ratio of the initiator to the vinyl-containing acid monomer is (0.01-0.1):1.
[0020] Preferably, the mass ratio of the graphene oxide nanosheets to the vinyl-containing amine monomer is 1:(1-200), and the mass ratio of the initiator to the vinyl-containing amine monomer is (0.01-0.1):1.
[0021] Preferably, the temperature of the free radical polymerization reaction is 60-100° C. and the time is 2-8 hours.
[0022] Preferably, the nanosheet assembly technique is vacuum filtration, spin coating or spray coating, but is not limited thereto.
[0023] Preferably, the mass ratio of the P1@GO nanosheet dispersion to the P2@GO nanosheet dispersion is 1:(0.1-10).
[0024] The second object of the present invention is to provide a two-dimensional ion pair membrane prepared according to the preparation method of the two-dimensional ion pair membrane.
[0025] The third object of the present invention is to provide application of the two-dimensional ion pair membrane in desalination.
[0026] The desalination is carried out by treating the salt solution using nanofiltration, forward osmosis or pervaporation technology.
[0027] The components of the salt solution include AB type, AB2 type and A2B type metal salts.
[0028] Preferably, the concentration of the salt solution is 0.02-1 mol·L -1 , but it is not limited to this.
[0029] Preferably, the metal salt is at least one of NaCl, KCl, LiCl, CaCl2, MgCl2, NiCl2, CdCl2, CuCl2, FeCl3, CrCl3, AlCl3, and Na2SO4, but is not limited thereto.
[0030] The principle of the present invention is: using graphene oxide as a substrate, respectively introducing polycarboxylic acid (polysulfonic acid) molecules and polypyridine (polytertiary amine) molecules between the layers of graphene oxide to prepare a two-dimensional ion pair membrane, because the carboxyl (sulfonic acid) group in the polycarboxylic acid (polysulfonic acid) will dissociate hydrogen ions, thereby protonating the pyridyl (tertiary amine) group in the polypyridine (polytertiary amine), thereby forming an ion pair. The formation of the ion pair plays a role in stabilizing the interlayer distance and inhibiting swelling, and on the other hand, does not provide adsorption sites, thereby improving the salt retention rate. In addition, the polycarboxylic acid (polysulfonic acid) molecules and polypyridine (polytertiary amine) molecules introduced between the layers of graphene oxide improve the hydrophilicity of the two-dimensional ion pair membrane, thereby improving the water flux.
[0031] In step 2, when the vinyl-containing acid monomer is AA, a PAA@GO nanosheet dispersion is obtained through the polymerization reaction.
[0032] In step 2, when the vinyl-containing acid monomer is SS, a PSS@GO nanosheet dispersion is obtained through the polymerization reaction.
[0033] In step 3, when the vinyl-containing amine monomer is 4VP, a P4VP@GO nanosheet dispersion is obtained through the polymerization reaction.
[0034] In step 3, when the vinyl-containing amine monomer is DMAA, a PDMAA@GO nanosheet dispersion is obtained through the polymerization reaction.
[0035] In step 5, the structural formula of the ion pair PAP formed by PAA@GO and P4VP@GO is as follows:
[0036]
[0037] In step 5, the structural formula of the ion pair PAD formed by PAA@GO and PDMAA is as follows:
[0038]
[0039] In step 5, the structural formula of the ion pair PSP formed by PSS@GO and P4VP@GO is as follows:
[0040]
[0041] In step 5, the structural formula of the ion pair PSD formed by PSS@GO and PDMAA@GO is as follows:
[0042]
[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0044] 1. The two-dimensional ion pair membrane of the present invention has a high salt rejection rate and a high water flux. Compared with the composite membranes reported in Nature Communications (Nature Communications, 2019, 10(1): 1-8) and Journal of the American Chemical Society (Journal of the American Chemical Society, 2021, 143(13): 5080-5090), the two-dimensional ion pair membrane of the present invention not only has a high rejection effect on AB2 or A2B ions, but also has a relatively high rejection rate for AB salts such as NaCl.
[0045] 2. Compared with the modified graphene oxide membrane based on anion and cation regulation disclosed in patent CN112957929A, the two-dimensional ion pair membrane of the present invention not only has a stable interlayer structure, but also has a higher water flux in the pervaporation desalination process, and the water flux can reach 28.2 kg·m at 60°C. -2 ·h -1 At the same time, the film making process is highly controllable and more conducive to mass production. Description of the drawings:
[0046] Figure 1 This is a surface scanning electron microscope (SEM) image of the two-dimensional ion pair membrane (PAP) obtained in Example 1;
[0047] Figure 2 This is a cross-sectional scanning electron microscope image (SEM) of the two-dimensional ion pair membrane (PAP) obtained in Example 1;
[0048] Figure 3 This is the infrared spectrum (FTIR) of the two-dimensional ion pair membrane (PAP) obtained in Example 1. Specific implementation method:
[0049] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0050] Example 1
[0051] In this embodiment, the two-dimensional ion pair membrane PAP is prepared according to the following steps:
[0052] Step 1: Weigh 20 mg of graphene oxide powder and disperse it in deionized water by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.5 mg mL-1 Graphene oxide nanosheet dispersion.
[0053] Step 2: Weigh 20 mg of graphene oxide powder and disperse it in N,N-dimethylformamide by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.1 mg mL -1 Graphene oxide nanosheet dispersion.
[0054] Step 3: Add 2 g of acrylic acid (the mass ratio of graphene oxide nanosheets to acrylic acid is 1:100) and 100 mg of initiator potassium persulfate (the mass ratio of potassium persulfate to acrylic acid is 0.05:1) to the graphene oxide nanosheet dispersion obtained in step 1, and stir evenly to obtain reaction solution 1.
[0055] Step 4, add 200 mg of 4-vinylpyridine (the mass ratio of graphene oxide nanosheets to 4-vinylpyridine is 1:10) and 10 mg of initiator azobisisobutyronitrile (the mass ratio of azobisisobutyronitrile to 4-vinylpyridine is 0.05:1) to the graphene oxide nanosheet dispersion obtained in step 2, and stir evenly to obtain reaction solution 2.
[0056] Step 5: Under N2 protection, the reaction solution 1 obtained in step 3 was placed in a single-necked flask, and reacted in an oil bath at 65°C for 6 h to obtain a PAA@GO nanosheet dispersion.
[0057] Step 6: Under N2 protection, the reaction solution 2 obtained in step 4 was placed in a single-necked flask, and reacted in an oil bath at 85°C for 4 h to obtain a P4VP@GO nanosheet dispersion.
[0058] Step 7: The PAA@GO and P4VP@GO nanosheet dispersions obtained in steps 5 and 6 were mixed in a ratio of 1:10 and loaded on a polyvinylidene fluoride substrate with a pore size of 220 nm by vacuum filtration. The mixture was dried at 50°C for 12 h to remove excess solvent, thereby obtaining a two-dimensional ion pair membrane PAP.
[0059] Figure 1 This is a surface scanning electron microscope (SEM) image of the two-dimensional ion pair membrane PAP obtained in Example 1. It can be observed that the surface is smooth and has no defects.
[0060] Figure 2 This is a cross-sectional scanning electron microscope (SEM) image of the two-dimensional ion pair membrane PAP obtained in Example 1. A uniform two-dimensional layered structure can be observed, and the membrane thickness is about 650 nm.
[0061] Figure 3This is the infrared spectrum (FTIR) of the two-dimensional ion pair membrane PAP obtained in Example 1. It can be seen from the figure that the stretching vibration peak of the carboxyl group in the two-dimensional ion pair membrane PAP has a blue shift, and the stretching vibration peak of the CN bond has a red shift, which proves the formation of ion pairs.
[0062] The two-dimensional ion pair membrane PAP of this example is used to separate the salt solution of NaCl: the two-dimensional ion pair membrane PAP obtained in this example is placed in a nanofiltration device, and the treatment concentration is 0.05 mol·L -1 The results show that the two-dimensional ion pair membrane PAP obtained in this example has a NaCl rejection rate of 56.22% and a water flux of 7.6 kg·m -2 ·h -1 The rejection rate of pure graphene oxide membrane for NaCl is 16.20%, and the water flux is 5.7 kg·m -2 ·h -1 .
[0063] Example 2
[0064] In this example, a two-dimensional ion pair membrane PAP was prepared in the same manner as in Example 1.
[0065] The two-dimensional ion pair membrane PAP of this embodiment is applied to separate the salt solution of Na2SO4: the two-dimensional ion pair membrane PAP obtained in this embodiment is placed in a nanofiltration device, and the treatment concentration is 0.05 mol·L -1 The results show that the two-dimensional ion pair membrane PAP obtained in this example has a Na2SO4 retention rate of 60.75% and a water flux of 7.2 kg·m -2 ·h -1 ; The rejection rate of pure graphene oxide membrane for Na2SO4 is 18.45%, and the water flux is 5.1kg·m -2 ·h -1 .
[0066] Example 3
[0067] In this example, a two-dimensional ion pair membrane PAP was prepared by the same method as in Example 1.
[0068] The two-dimensional ion pair membrane PAP of this example is applied to separate the salt solution of MgCl2: the two-dimensional ion pair membrane PAP obtained in this example is placed in a nanofiltration device, and the treatment concentration is 0.05 mol·L -1 The results show that the two-dimensional ion pair membrane PAP obtained in this example has a MgCl2 rejection rate of 57.28% and a water flux of 7.2 kg·m -2 ·h -1The rejection rate of pure graphene oxide membrane for MgCl2 is 18.1%, and the water flux is 5.2 kg·m -2 ·h -1 .
[0069] Example 4
[0070] In this example, a two-dimensional ion pair membrane PAP was prepared by the same method as in Example 1.
[0071] The ion pair membrane PAP of this example is applied to forward osmosis desalination: the two-dimensional ion pair membrane PAP obtained in this example is placed in a forward osmosis device, and a concentration of 0.1 mol·L -1 NaCl salt solution and 2 mol·L -1 Sucrose solution. The results show that the two-dimensional ion pair membrane PAP obtained in this example has a NaCl rejection rate of 94.48% and a water flux of 6.2 kg·m -2 ·h -1 ; The rejection rate of pure graphene oxide membrane for NaCl is only 57.15%, and the water flux is 4.5 kg·m -2 ·h -1 .
[0072] Example 5
[0073] In this embodiment, the two-dimensional ion pair membrane PAP is prepared in the same manner as in embodiment 1.
[0074] The two-dimensional ion pair membrane (PAP) of this embodiment is applied to pervaporation desalination: the two-dimensional ion pair membrane (PAP) obtained in this embodiment is placed in a pervaporation device, the feed liquid is a NaCl solution with a concentration of 3.5wt%, and the feed liquid temperature is 60°C. The results show that the two-dimensional ion pair membrane (PAP) obtained in this embodiment has a NaCl rejection rate of 99.93% and a water flux of 28.2kg·m -2 ·h -1 , while the rejection rate of pure graphene oxide membrane for NaCl is 99.92% and the water flux is 20.9 kg·m -2 ·h -1 .
[0075] Example 6
[0076] In this embodiment, the two-dimensional ion pair membrane PAD is prepared according to the following steps:
[0077] Step 1: Weigh 20 mg of graphene oxide powder and disperse it in deionized water by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.5 mg mL -1 Graphene oxide nanosheet dispersion.
[0078] Step 2: Weigh 20 mg of graphene oxide powder and disperse it in N,N-dimethylformamide by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.1 mg mL -1 Graphene oxide nanosheet dispersion.
[0079] Step 3: Add 2 g of acrylic acid (the mass ratio of graphene oxide nanosheets to acrylic acid is 1:100) and 100 mg of initiator potassium persulfate (the mass ratio of potassium persulfate to acrylic acid is 0.05:1) to the graphene oxide nanosheet dispersion obtained in step 1, and stir evenly to obtain reaction solution 1.
[0080] Step 4: Add 200 mg of dimethylallylamine (the mass ratio of graphene oxide nanosheets to dimethylallylamine is 1:10) and 10 mg of initiator azobisisobutyronitrile (the mass ratio of azobisisobutyronitrile to dimethylallylamine is 0.05:1) to the dispersion of graphene oxide nanosheets obtained in step 2, and stir evenly to obtain reaction solution 2.
[0081] Step 5: Under N2 protection, the reaction solution 1 obtained in step 3 was placed in a single-necked flask, and reacted in an oil bath at 65°C for 6 h to obtain a PAA@GO nanosheet dispersion.
[0082] Step 6: Under N2 protection, the reaction solution 2 obtained in step 4 was placed in a single-necked flask, and reacted in an oil bath at 65°C for 6 h to obtain a PMDAA@GO nanosheet dispersion.
[0083] Step 7. The PAA@GO and PMDAA@GO dispersions obtained in steps 5 and 6 were mixed in a ratio of 1:10 and loaded on a polyvinylidene fluoride substrate with a pore size of 220 nm by vacuum filtration. The mixture was dried at 50°C for 12 h to remove excess solvent, thereby obtaining a two-dimensional ion pair membrane PAD.
[0084] The two-dimensional ion pair membrane PAD of this example is used to separate the salt solution of NaCl: the two-dimensional ion pair membrane PAD obtained in this example is placed in a nanofiltration device to treat 0.05 mol·L -1 The results show that the two-dimensional ion pair membrane PAD obtained in this example has a NaCl rejection rate of 54.68% and a water flux of 7.8 kg·m -2 ·h -1 , while the rejection rate of pure graphene oxide membrane for NaCl is 16.20% and the water flux is 5.7 kg·m -2 ·h -1 .
[0085] Example 7
[0086] In this example, a two-dimensional ion pair membrane PAD is prepared by the same method as in Example 6.
[0087] The two-dimensional ion pair membrane PAD of this embodiment is applied to forward osmosis desalination: the two-dimensional ion pair membrane PAD obtained in this embodiment is placed in a forward osmosis device, and a concentration of 0.1 mol·L -1 NaCl salt solution and 2 mol·L -1 Sucrose solution. The results show that the two-dimensional ion pair membrane PAD obtained in this example has a NaCl rejection rate of 92.62% and a water flux of 6.0 kg·m -2 ·h -1 ; The rejection rate of pure graphene oxide membrane for NaCl is only 57.15%, and the water flux is 4.5 kg·m -2 ·h -1 .
[0088] Example 8
[0089] In this example, a two-dimensional ion pair membrane PAD is prepared by the same method as in Example 6.
[0090] The two-dimensional ion pair membrane PAD of this embodiment is applied to pervaporation desalination: the two-dimensional ion pair membrane PAD obtained in this embodiment is placed in a pervaporation device, the feed liquid is a NaCl solution with a concentration of 3.5wt%, and the feed liquid temperature is 60℃. The results show that the two-dimensional ion pair membrane PAD obtained in this embodiment has a NaCl rejection rate of 99.89% and a water flux of 29.4kg·m -2 ·h -1 The pure graphene oxide membrane has a NaCl rejection rate of 99.92% and a water flux of 20.9 kg·m -2 ·h -1 .
[0091] Example 9
[0092] In this embodiment, the two-dimensional ion pair membrane PSP is prepared according to the following steps:
[0093] Step 1: Weigh 20 mg of graphene oxide powder and disperse it in deionized water by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.5 mg mL -1 Graphene oxide nanosheet dispersion.
[0094] Step 2: Weigh 20 mg of graphene oxide powder and disperse it in N,N-dimethylformamide by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.1 mg mL -1 Graphene oxide nanosheet dispersion.
[0095] Step 3: Add 2 g of styrene sulfonic acid (the mass ratio of graphene oxide nanosheets to styrene sulfonic acid is 1:100) and 100 mg of initiator potassium persulfate (the mass ratio of potassium persulfate to styrene sulfonic acid is 0.05:1) to the graphene oxide nanosheet dispersion obtained in step 1, and stir evenly to obtain reaction solution 1.
[0096] Step 4, add 200 mg of 4-vinyl pyridine (the mass ratio of graphene oxide nanosheets to 4-vinyl pyridine is 1:10) and 10 mg of initiator azobisisobutyronitrile (the mass ratio of azobisisobutyronitrile to 4-vinyl pyridine is 0.05:1) to the dispersion of graphene oxide nanosheets obtained in step 2, and stir evenly to obtain reaction solution 2.
[0097] Step 5: Under N2 protection, the reaction solution 1 obtained in step 3 was placed in a single-necked flask and reacted in an oil bath at 70°C for 4 h to obtain a PSS@GO nanosheet dispersion.
[0098] Step 6: Under N2 protection, the reaction solution 2 obtained in step 4 was placed in a single-necked flask and reacted in an oil bath at 85°C for 4 h to obtain a P4VP@GO nanosheet dispersion.
[0099] Step 7. The PSS@GO and P4VP@GO dispersions obtained in steps 5 and 6 were mixed in a ratio of 1:10 and loaded on a polyvinylidene fluoride substrate with a pore size of 220 nm by vacuum filtration. The mixture was dried at 50°C for 12 h to remove excess solvent, thereby obtaining a two-dimensional ion pair membrane PSP.
[0100] The two-dimensional ion pair membrane PSP of this embodiment is applied to separate the salt solution of NaCl: the two-dimensional ion pair membrane PSP obtained in this embodiment is placed in a nanofiltration device, and the treatment concentration is 0.05 mol·L -1 The results show that the two-dimensional ion pair membrane PSP obtained in this example has a NaCl rejection rate of 61.14% and a water flux of 7.1 kg·m -2 ·h -1 The rejection rate of pure graphene oxide membrane for NaCl is 16.20%, and the water flux is 5.7 kg·m -2 ·h -1 .
[0101] Example 10
[0102] In this example, a two-dimensional ion pair membrane PSP was prepared in the same manner as in Example 9.
[0103] The two-dimensional ion pair membrane PSP of this embodiment is applied to forward osmosis desalination: the two-dimensional ion pair membrane PSP obtained in this embodiment is placed in a forward osmosis device, and a 0.1 mol·L-1 NaCl salt solution and 2 mol·L -1 Sucrose solution. The results show that the two-dimensional ion pair membrane PSP obtained in this example has a NaCl rejection rate of 91.90% and a water flux of 6 kg·m -2 ·h -1 ; The rejection rate of pure graphene oxide membrane for NaCl is only 57.15%, and the water flux is 4.5 kg·m -2 ·h -1 .
[0104] Embodiment 11
[0105] In this example, a two-dimensional ion pair membrane PSP was prepared in the same manner as in Example 9.
[0106] The two-dimensional ion pair membrane PSP of this embodiment is applied to pervaporation desalination: the two-dimensional ion pair membrane PSP obtained in this embodiment is placed in a pervaporation device, the feed liquid is a NaCl solution with a concentration of 3.5wt%, and the feed liquid temperature is 60°C. The results show that the two-dimensional ion pair membrane PSP obtained in this embodiment has a NaCl rejection rate of 99.95% and a water flux of 27.6kg·m -2 ·h -1 The pure graphene oxide membrane has a NaCl rejection rate of 99.92% and a water flux of 20.9 kg·m -2 ·h -1 .
[0107] Example 12
[0108] In this embodiment, the two-dimensional ion pair membrane PSD is prepared according to the following steps:
[0109] Step 1: Weigh 20 mg of graphene oxide powder and disperse it in deionized water by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.5 mg mL -1 Graphene oxide nanosheet dispersion.
[0110] Step 2: Weigh 20 mg of graphene oxide powder and disperse it in N,N-dimethylformamide by ultrasonication to obtain a dispersion of graphene oxide nanosheets. The ultrasonic temperature is 30 °C and the ultrasonic time is 2 h. The concentration is 0.1 mg mL -1 Graphene oxide nanosheet dispersion.
[0111] Step 3: Add 2 g of styrene sulfonic acid (the mass ratio of graphene oxide nanosheets to styrene sulfonic acid is 1:100) and 100 mg of initiator potassium persulfate (the mass ratio of potassium persulfate to styrene sulfonic acid is 0.05:1) to the graphene oxide nanosheet dispersion obtained in step 1, and stir evenly to obtain reaction solution 1.
[0112] Step 4: Add 200 mg of dimethylallylamine (the mass ratio of graphene oxide nanosheets to dimethylallylamine is 1:10) and 10 mg of initiator azobisisobutyronitrile (the mass ratio of azobisisobutyronitrile to dimethylallylamine is 0.05:1) to the dispersion of graphene oxide nanosheets obtained in step 2, and stir evenly to obtain reaction solution 2.
[0113] Step 5: Under N2 protection, the reaction solution 1 obtained in step 3 was placed in a single-necked flask, and reacted in an oil bath at 70°C for 4 h to obtain a PSS@GO nanosheet dispersion.
[0114] Step 6: Under N2 protection, the reaction solution 2 obtained in step 4 was placed in a single-necked flask, and reacted in an oil bath at 65°C for 6 h to obtain a PMDAA@GO nanosheet dispersion.
[0115] Step 7. The PSS@GO and PMDAA@GO dispersions obtained in steps 5 and 6 were mixed in a ratio of 1:10 and loaded on a polyvinylidene fluoride substrate with a pore size of 220 nm by vacuum filtration. The mixture was dried at 50°C for 12 h to remove excess solvent, thereby obtaining a two-dimensional ion pair membrane PSD.
[0116] The two-dimensional ion pair membrane PSD of this example is used to separate the salt solution of NaCl: the two-dimensional ion pair membrane PSD obtained in this example is placed in a nanofiltration device, and the treatment concentration is 0.05 mol·L -1 The results show that the two-dimensional ion pair membrane PSD obtained in this example has a NaCl rejection rate of 60.48% and a water flux of 7.1 kg·m -2 ·h -1 The rejection rate of pure graphene oxide membrane for NaCl is 16.20%, and the water flux is 5.7 kg·m -2 ·h -1 .
[0117] Embodiment 13
[0118] In this example, a two-dimensional ion pair membrane PSD is prepared using the same method as in Example 12.
[0119] The two-dimensional ion pair membrane PSD of this embodiment is applied to forward osmosis desalination: the two-dimensional ion pair membrane PSD obtained in this embodiment is placed in a forward osmosis device, and a 0.1 mol·L -1 NaCl salt solution and 2 mol·L -1 Sucrose solution. The results show that the two-dimensional ion pair membrane PSD obtained in this example has a NaCl rejection rate of 92.11% and a water flux of 5.7 kg·m -2 ·h-1 ; The rejection rate of pure graphene oxide membrane for NaCl is only 57.15%, and the water flux is 4.5 kg·m -2 ·h -1 .
[0120] Embodiment 14
[0121] In this example, a two-dimensional ion pair membrane PSD is prepared using the same method as in Example 12.
[0122] The two-dimensional ion pair membrane PSD of this embodiment is applied to pervaporation desalination: the two-dimensional ion pair membrane PSD obtained in this embodiment is placed in a pervaporation device, the feed liquid is a NaCl solution with a concentration of 3.5wt%, and the feed liquid temperature is 60°C. The results show that the two-dimensional ion pair membrane PSD obtained in this embodiment has a NaCl rejection rate of 99.88% and a water flux of 28.1kg·m -2 ·h -1 The pure graphene oxide membrane has a NaCl rejection rate of 99.92% and a water flux of 20.9 kg·m -2 ·h -1 .
[0123] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a two-dimensional ion pair membrane, characterized in that: A vinyl-containing acid monomer is added to a graphene oxide nanosheet dispersion, and a free radical polymerization reaction is carried out under the initiation of an initiator to obtain a P1@GO nanosheet dispersion; an vinyl-containing amine monomer is added to the graphene oxide nanosheet dispersion, and a free radical polymerization reaction is carried out under the initiation of an initiator to obtain a P2@GO nanosheet dispersion; and then the P1@GO nanosheet dispersion and the P2@GO nanosheet dispersion are mixed in proportion and deposited on a porous substrate membrane by a nanosheet assembly technology to obtain a two-dimensional ion pair membrane.
2. The preparation method according to claim 1, characterized in that: The porous substrate membrane is selected from one of nylon membrane, polyethersulfone membrane, polyvinylidene fluoride membrane, polycarbonate membrane, anodized aluminum membrane and polyacrylonitrile membrane, and the pore size of the porous substrate membrane is 50-450 nm.
3. The preparation method according to claim 1, characterized in that: The vinyl-containing acid monomer is a vinyl-containing carboxylic acid or sulfonic acid monomer; The vinyl-containing amine monomer is a vinyl-containing pyridine or tertiary amine monomer.
4. The preparation method according to claim 3, characterized in that: The vinyl-containing acid monomer is acrylic acid, p-styrene sulfonic acid, propylene sulfonic acid or 4-vinylbenzoic acid; The vinyl-containing amine monomer is 4-vinylpyridine, dimethylallylamine or 4-dimethylaminostyrene.
5. The preparation method according to claim 1, characterized in that: The graphene oxide nanosheet dispersion is prepared by ultrasonically dispersing graphene oxide powder in deionized water or an organic solvent.
6. The preparation method according to claim 5, characterized in that: The concentration of the graphene oxide nanosheet dispersion is 0.05-1 mg·mL -1 .
7. The preparation method according to claim 5, characterized in that: The temperature of the ultrasound is 20-50°C, and the time is 0.5-3 h.
8. The preparation method according to claim 5, characterized in that: The organic solvent is one of N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.
9. The preparation method according to claim 1, characterized in that: The mass ratio of the graphene oxide nanosheets to the vinyl acid monomer is 1: (1-200), and the mass ratio of the initiator to the vinyl acid monomer is (0.01-0.1): 1; The mass ratio of the graphene oxide nanosheets to the vinyl-containing amine monomer is 1: (1-200), and the mass ratio of the initiator to the vinyl-containing amine monomer is (0.01-0.1):
1.
10. The preparation method according to claim 1, characterized in that: The temperature of the free radical polymerization reaction is 60-100° C. and the time is 2-8 h.
11. The preparation method according to claim 1, characterized in that: The nanosheet assembly technology is vacuum filtration, spin coating or spray coating.
12. The preparation method according to claim 1, characterized in that: The mass ratio of the P1@GO nanosheet dispersion to the P2@GO nanosheet dispersion is 1: (0.1-10).
13. A two-dimensional ion pair membrane prepared according to the preparation method according to any one of claims 1 to 12.
14. Use of the two-dimensional ion pair membrane according to claim 13 in desalination.
15. The use according to claim 14, characterized in that: The desalination is to treat the salt solution by nanofiltration, forward osmosis or pervaporation process; The components of the salt solution include AB type, AB2 type and A2B type metal salts.
16. The use according to claim 15, characterized in that: The concentration of the salt solution is 0.02-1 mol·L -1 .
17. The use according to claim 15, characterized in that: The metal salt is at least one of NaCl, KCl, LiCl, CaCl2, MgCl2, NiCl2, CdCl2, CuCl2, FeCl3, CrCl3, AlCl3, and Na2SO4.
Citation Information
Patent Citations
Ionic polymer and graphene oxide nano composite film and preparation method and application thereof
CN109364774A
Preparation method and application of sulfonated polymer cross-linked network embedded graphene oxide-based two-dimensional composite film
CN110756067A